Ceratium furcoides (Levander) Langhans in reservoirs at the Ebro watershed, Spain and Sao Paulo state, Brazil - Sendra, María Dolores; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo L. M.; Soria, Xavier; Soria, Juan Miguel; Vicente, Eduardo (Asociacion Iberica de Limnologia, 2022)
This study compares the morphological characteristics of the dinoflagellate Ceratium furcoides from three Ebro basin reservoirs (Spain) and from six reservoirs at São Paulo state (Brazil) with the aim to identify the distinct morphotypes of Ceratium furcoides in Spain and Brazil. We studied the physical and chemical variables to determine the trophic state of each reservoir. Unlike Ceratium hirundinella, Ceratium furcoides is not a frequent species within the plankton community at Ebro Basin reservoirs, however, this species has been responsible of one monospecific bloom at El Val reservoir. Nevertheless, both Ce-ratium species are considered invasive in South America. Ceratium furcoides has displaced C. hirundinella at São Paulo state reservoirs, reaching high densities, to the extent of forming monospecific blooms. Morphometric analysis was performed by optic and electronic microscopy (DIC and SEM respectively). The analysis shows significant differences in: I) total cell length, ii) horns length and iii) presence or absence of a fourth horn. While the microscopic study allows differentiating morphotypes according to the reservoir typology, a deeper study using molecular genetic techniques on the different populations of C. furcoides would allow to know better the relationship between the dinoflagellate dynamics and the reservoirs trophic states.
Ceratium furcoides (Levander) Langhans en embalses de la cuenca del Ebro en España y embalses del estado de Sao Paulo en Brasil
Keywords: Algal blooms; Ceratium furcoides; Morphotypes; Reservoirs